ANALISIS PENERAPAN PROGRAM MBG DALAM MEMBENTUK 7 KEBIASAAN ANAK HEBAT DI SD NEGERI BABAKAN 01 - Fitria Khoirun Nisa; Farhan Saefudin Wahid; Laelia Nurpratiwiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the implementation of the Free Nutritious Meal Program (MBG) and the 7 Habits of Great Indonesian Children Movement at SD Negeri Babakan 01 as an effort to shape character and improve the quality of primary education. The MBG program is carried out routinely by providing nutritious meals to students, which has been proven to enhance learning concentration, enthusiasm, and the development of healthy habits. Meanwhile, the 7 Habits program instills discipline, independence, social awareness, and responsibility through daily activities such as waking up early, worship, exercising, eating nutritious food, studying diligently, engaging in community life, and going to bed earlier. The research method used is qualitative with a case study design, employing observation, interviews, and documentation. Findings show that the combination of MBG and the 7 Habits program significantly contributes to the formation of positive student character, improves health, and supports more effective learning processes. The role of teachers, schools, and parents is crucial in ensuring the success of these programs. In conclusion, MBG is not only a program to fulfill nutritional needs but also a character education strategy aligned with the vision of Indonesia Emas 2045. Suggested improvements include enhancing the quality and variety of menus to meet children’s nutritional needs and strengthening coordination between schools and families to sustain healthy habits at home. This program has the potential to serve as a model for other schools in nurturing a generation that is healthy, intelligent, and morally upright.